New American Lamiinae (Coleoptera, Cerambycidae) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
Five new species are described in Lamiinae: Cotycicuiara v-alba (Acanthoderini), from Brazil (Bahia); Dolichestola birai, from Argentina, and D. monnei, from Brazil (Rio de Janeiro) and Uruguay (Desmiphorini); Blabicentrus lineatus, from Brazil (Rio de Janeiro) (Desmiphorini); and Inermestoloides flavus, from Brazil (Pará) (Desmiphorini). A key to species of Cotycicuiara is provided; Blabicentrus lineatus is included in a previous key.